2018
DOI: 10.1002/jcp.27779
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid poly‐l‐lactic acid/poly(ε‐caprolactone) nanofibrous scaffold can improve biochemical and molecular markers of human induced pluripotent stem cell‐derived hepatocyte‐like cells

Abstract: A suitable alternative strategy for liver transplantation is the use of nanofibrous scaffolds together with stem cells. In this study, a random hybrid of poly‐l‐lactic acid (PLLA) and poly(ε‐caprolactone) (PCL) was used as a three‐dimensional (3D) culture for differentiation of hepatocyte‐like cells and compared with routine culture (two‐dimensional [2D]). The expression of the endodermal marker, forkhead box A2 (FOXA2), was assessed on Day 3 and the hepatic markers; albumin (ALB), α‐1 antitrypsin (AAT), and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The more recent protocols have relied on the use of decellularized scaffolds or extra cellular matrix components, such as laminins and collagens, to which iPSCs can attach in order to mimic the liver microenvironment during hepatocyte differentiation [44][45][46]. Moreover, other approaches have been explored using 3D scaffolds of synthetic origins, such as hydrogel or other nanofibers scaffolds, resulting in the generation of a more mature phenotype compared to 2D cultures systems, which are able to activate the expression of CYP450 and other mature liver markers [47,48]. Despite the promising results, 3D driven hepatocyte generation is impaired by the poor standardization protocols during scaffold manufacturing.…”
Section: Hepatocytesmentioning
confidence: 99%
“…The more recent protocols have relied on the use of decellularized scaffolds or extra cellular matrix components, such as laminins and collagens, to which iPSCs can attach in order to mimic the liver microenvironment during hepatocyte differentiation [44][45][46]. Moreover, other approaches have been explored using 3D scaffolds of synthetic origins, such as hydrogel or other nanofibers scaffolds, resulting in the generation of a more mature phenotype compared to 2D cultures systems, which are able to activate the expression of CYP450 and other mature liver markers [47,48]. Despite the promising results, 3D driven hepatocyte generation is impaired by the poor standardization protocols during scaffold manufacturing.…”
Section: Hepatocytesmentioning
confidence: 99%
“…Cell culture compatible hydrogels allow for cells to be suspended in a liquid gel which later solidify, allowing for cells to aggregate and proliferate into the hydrogel matrix (44). Cells can also be seeded directly onto pre-constructed polymer scaffolds which are either entirely synthetic, or are hybrid structures treated with ECM components prior to cell seeding (45, 46). Hepatocytes differentiated in 3D ECM based scaffolds showed significantly greater expression of mature liver markers and greater CYP450 enzyme activity compared to standard 2D cultures (44, 4749).…”
Section: Hepatic Differentiation Of Ipscs In Vitromentioning
confidence: 99%
“…To overcome these limitations, many reports have indicated the possible application of PLLA/ poly(£-caprolactone) blends. 99,100 Ranucci and Moghe 101 cultured hepatocytes on porous foams of amorphous PLGA with a wide range of controlled pore-size distributions (approximately 1 to 100 microns) and found that foams with supercellular size voids (~67 microns) promoted the kinetics of 3D aggregation with the most rapid and sustained albumin secretory kinetics. Kasuya et al 102 developed a 3D stacked culture method using biodegradable PLGA membranes.…”
Section: Synthetic Polymersmentioning
confidence: 99%